Polymer composition, molded body and method for producing molded body

By using a multi-copolymer system of 4-methyl-1-pentene copolymer A, B and C with a specific content range, the problem that 4-methyl-1-pentene copolymer is prone to heat shrinkage after heat treatment is solved, and the low heat shrinkage and high mechanical properties of the molded body are achieved, and it is suitable for applications that require high thermal stability and transparency.

JP2025043901APending Publication Date: 2025-04-01MITSUI CHEMICALS INC

Patent Information

Application Number
JP2023151475
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing 4-methyl-1-pentene copolymer is prone to heat shrinkage after heat treatment, and it is difficult to form high-quality molded bodies during blow molding.

Method used

A multi-copolymer system consisting of 4-methyl-1-pentene copolymers A, B and C is adopted, and the structural unit content of copolymers A, B and C is 97.5-100 mol%, 91.0-97.5 mol%, and 75.0-91.0 mol%, respectively. The thermal stability and transparency of the molded body are improved by adjusting the phase composition and melting point of the copolymer.

Benefits of technology

The 4-methyl-1-pentene copolymer molded body is achieved with low heat shrinkage and high mechanical properties, which improves the transparency and thermal stability of the molded body, and is suitable for applications that require high thermal stability and transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043901000001
    Figure 2025043901000001
  • Figure 2025043901000002
    Figure 2025043901000002
Patent Text Reader

Abstract

To provide a polymer composition having excellent moldability which can form a molded body having low heat shrinkability while being excellent in mechanical properties, impact resistance, transparency and heat resistance in a balanced manner.SOLUTION: There is provided a polymer composition which comprises 15 to 45 mass% of a copolymer satisfying (A-i) to (A-ii) and 35 to 80 mass% of a copolymer satisfying (B-i) to (B-iii) and 5 to 30 mass% of a copolymer satisfying (C-i) to (C-iii). (A-i) The content of a constitutional unit (i) derived from 4-methyl-1-pentene is 97.5 mol% or more and less than 100 mol% and the content of a constitutional unit (ii) derived from an α-olefin having 2 to 20 carbon atoms is more than 0 mol% and 2.5 mol% or less. (A-ii): The intrinsic viscosity is 1.0 to 5.0 dl / g. (B-i): The content of the constitutional unit (i) is 91.0 mol% or more and less than 97.5 mol% and the content of the constitutional unit (ii) is more than 2.5 mol% and 9.0 mol% or less. (B-ii): The intrinsic viscosity is 2.0 to 5.0 dl / g. (B-iii): The melting point is 180°C or more and less than 210°C. (C-i): The content of the constitutional unit (i) is 75.0 mol% or more and less than 91.0 moll% and the content of the constitutional unit (ii) is more than 9.0 mol% and 25.0 mol% or less. (C-ii): The intrinsic viscosity is 0.1 dl / g or more and less than 2.0 dl / g. (C-iii): No melting point is observed.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer composition, a molded article, and a method for producing a molded article. [Background technology]

[0002] 4-Methyl-1-pentene (co)polymer is a resin that has excellent characteristics compared to polyethylene and polypropylene, such as heat resistance, transparency, light weight, chemical resistance, release properties, stain resistance, steam resistance, gas permeability, and electrical properties, and is used in a wide range of fields, such as food containers, secondary materials for electronic and information components, laboratory equipment, stationery, crosslinking process materials, release films, films for electronic and information components, food packaging materials, synthetic paper, and cages.

[0003] Conventionally, polyolefins such as polyethylene and polypropylene and polyesters such as polyethylene terephthalate have been mainly used as raw materials for resin containers. For example, polyolefins such as polyethylene and polypropylene are widely used for liquid containers, fuel tanks, etc., and are generally molded by injection molding or blow molding. However, the molded articles have often been inferior in transparency.

[0004] On the other hand, polyesters such as polyethylene terephthalate are widely used mainly as beverage containers, and are molded by injection blow molding (hereinafter also referred to as "injection blow molding"). In this molding method, a molded body called a preform is produced by injection molding, and then the preform is reheated and blow molded to produce a molded body. However, although the molded body has excellent transparency, it has a problem with heat resistance.

[0005] Here, in order to impart heat resistance to polyethylene terephthalate, a molded article is also produced using a composition in which engineering plastics such as polycarbonate and polyether sulfide are added to polyethylene terephthalate. However, such molded articles are only used for some applications due to the hygienic and cost aspects caused by residual monomers.

[0006] In recent years, various studies have been conducted on injection blow molded articles using polypropylene in order to obtain molded articles that overcome the drawback of polyethylene terephthalate in terms of heat resistance. However, in the case of polypropylene, since the molding temperature range is narrow, handling during molding is often difficult. In addition, when homopolypropylene is used, it is difficult to obtain molded articles with excellent transparency, and when random polypropylene is used, heat resistance is low, and there are problems in that usable polypropylenes (types, physical properties, etc.) are limited.

[0007] In order to solve the problems related to the transparency and heat resistance, studies have been conducted on molded articles using 4-methyl-1-pentene (co)polymers. However, when a molded article is obtained from a 4-methyl-1-pentene (co)polymer by blow molding, the 4-methyl-1-pentene (co)polymer has a high melting point and a low melt tension compared to polyethylene and polypropylene, which are the same polyolefins, and thus molding is difficult. For example, when attempting to mold a 4-methyl-1-pentene (co)polymer by blow molding such as injection blow molding, the 4-methyl-1-pentene (co)polymer solidifies after forming a preform and before blow molding, making molding difficult.

[0008] As a technique for solving such problems, Patent Document 1 describes a 4-methyl-1-pentene (co)polymer composition in which a 4-methyl-1-pentene (co)polymer and a 4-methyl-1-pentene / α-olefin copolymer are blended in a specific ratio, and describes that a blown molded article made of the composition has excellent transparency, heat resistance, toughness, and dimensional stability.

[0009] Patent Document 2 describes that a polymer composition containing two types of 4-methyl-1-pentene (co)polymers having specific physical properties has high impact resistance while having transparency and rigidity, and further has high heat resistance.

[0010] Patent Document 3 describes that specific 4-methyl-1-pentene polymer particles can reduce the rigidity, i.e., improve the flexibility, without impairing the properties such as high stereoregularity and excellent heat resistance. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] International Publication No. 2013 / 099876 [Patent Document 2] JP 2018-162408 A [Patent Document 3] International Publication No. 2019 / 198694 Summary of the Invention [Problem to be solved by the invention]

[0012] Depending on the application, the molded article may be sterilized by heating (for example, at 121° C.) before use, and is required to be resistant to deformation, particularly heat shrinkage, caused by such heating. However, molded articles made from the 4-methyl-1-pentene copolymers and the like described in the above patent documents tend to be susceptible to thermal shrinkage, and in this respect there is room for improvement.

[0013] The present invention has been made in consideration of the above, and an object of the present invention is to provide a polymer composition having excellent moldability, which is capable of forming a molded article having low heat shrinkage while being excellent in a well-balanced manner in mechanical properties, impact resistance, transparency, and heat resistance. [Means for solving the problem]

[0014] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by the following embodiments, and have completed the present invention.

[0015] [1] 15 to 45 mass% of a 4-methyl-1-pentene copolymer (A) satisfying the following requirements (Ai) and (A-ii); 35 to 80 mass% of a 4-methyl-1-pentene copolymer (B) satisfying the following requirements (Bi) to (B-iii); 5 to 30% by mass of a 4-methyl-1-pentene copolymer (C) satisfying the following requirements (Ci) to (C-iii) (wherein the total of the copolymers (A) to (C) is 100% by mass): The polymer composition (X) comprises: Requirement (Ai): The content of structural units (i) derived from 4-methyl-1-pentene is 97.5 mol% or more and less than 100 mol%, and the content of structural units (ii) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 0 mol% and 2.5 mol% or less (the total content of the structural units (i) and (ii) is 100 mol%). Requirement (A-ii): Intrinsic viscosity [η] measured in decalin at 135°C A is 1.0-5.0 dl / g Requirement (Bi): The content of structural units (iii) derived from 4-methyl-1-pentene is 91.0 mol% or more and less than 97.5 mol%, and the content of structural units (iv) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 2.5 mol% and not more than 9.0 mol% (the total content of the structural units (iii) and the structural units (iv) is 100 mol%). Requirement (B-ii): Intrinsic viscosity [η] measured in decalin at 135°C B is 2.0-5.0 dl / g Requirement (B-iii): Melting point (Tm B ) is 180℃ or more and less than 210℃ Requirement (Ci): The content of the structural unit (v) derived from 4-methyl-1-pentene is 75.0 mol% or more and less than 91.0 mol%, and the content of the structural unit (vi) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 9.0 mol% and 25.0 mol% or less (the total content of the structural unit (v) and the structural unit (vi) is 100 mol%). Requirement (C-ii): Intrinsic viscosity [η] measured in decalin at 135°C C is 0.1 dl / g or more and less than 2.0 dl / g Requirement (C-iii): Melting point (Tm C ) is not observed

[0016] [2] the total content of all structural units (I) derived from 4-methyl-1-pentene contained in the polymer composition (X) is 90.0 to 96.0 mol%, the total content of all structural units (II) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) contained in the polymer composition (X) is 4.0 to 10.0 mol % (the total content of the structural units (I) and (II) is taken as 100 mol %); The polymer composition (X) according to [1].

[0017] [3] A molded article comprising the polymer composition (X) according to [1] or [2].

[0018] [4] The molded article according to [3], which is a blow molded article.

[0019] [5] A stretch blow molded article, The product of the stretch ratio in the longitudinal direction and the stretch ratio in the transverse direction of the stretch blow molded body is 1.2 to 6.0 times. The molded article according to [3].

[0020] [6] A step of forming a preform by injection molding the polymer composition (X) according to [1] or [2]; A step of forming a blow molded article by blow molding the obtained preform. A method for producing a molded body, comprising the steps of: Effect of the Invention

[0021] According to the present invention, it is possible to provide a polymer composition having excellent moldability (particularly blow moldability) and capable of forming a molded article having low heat shrinkage while having a well-balanced excellent mechanical properties (particularly tensile properties and bending properties), impact resistance, transparency, and heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] ≪Polymer composition (X)≫ The polymer composition (X) according to the present invention contains a 4-methyl-1-pentene copolymer (A), a 4-methyl-1-pentene copolymer (B) and a 4-methyl-1-pentene copolymer (C).

[0023] The total content of all structural units (I) derived from 4-methyl-1-pentene contained in the polymer composition (X) is preferably 90.0 to 96.0 mol %, more preferably 91.0 to 96.0 mol %, and even more preferably 92.0 to 96.0 mol %. The total content of all structural units (II) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) contained in the polymer composition (X) is preferably 4.0 to 10.0 mol%, more preferably 4.0 to 9.0 mol%, and even more preferably 4.0 to 8.0 mol%. However, the total content of the structural unit (I) and the structural unit (II) is 100 mol %. When the total content of the structural unit (II) is within the above range, a molded article having an excellent balance between stretchability and transparency can be easily formed.

[0024] In the copolymers (A) to (C), the structural units derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) are preferably structural units derived from the same kind of compound. By using the copolymers (A) to (C) containing structural units derived from such the same kind of compound, a molded article having excellent transparency can be easily obtained. The same type of compound is preferably a linear α-olefin having 6 to 20 carbon atoms, more preferably a linear α-olefin having 10 to 18 carbon atoms. Specifically, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, etc. are preferred, and 1-decene, 1-hexadecene, and 1-octadecene are more preferred.

[0025] The total content of the structural unit (I) can be calculated as the sum of the products of the content [mol %] of the structural unit derived from 4-methyl-1-pentene in each (co)polymer constituting the polymer composition (X) and the content [mass %] of each (co)polymer constituting the polymer composition (X) / 100. For example, copolymer (A) G having a content of the following structural unit (i) of a mol % A % by mass, and the content of the following structural unit (iii) is b % by mole. B % by mass, and the content of the following structural unit (v) is c mol %. C The total content of the structural units (I) in the polymer composition (X) consisting of % by mass can be calculated by the following formula. The total content of structural units (I) [mol%] = (a × G A +b×G B +c×G C +) / 100 The total content of the structural unit (II) can be calculated in the same manner. Note that the structural unit (II) corresponds to the following structural units (ii), (iv) and (vi).

[0026] The various compounds that are raw materials for the following copolymers (A) to (C) and the following additives may be compounds derived from fossil raw materials or compounds derived from biomass. Also, compounds derived from fossil raw materials and compounds derived from biomass may be used as raw materials for the following copolymers (A) to (C) and the following additives.

[0027] <4-methyl-1-pentene copolymer (A)> The 4-methyl-1-pentene copolymer (A) (hereinafter also referred to as "copolymer (A)") satisfies the following requirements (Ai) and (A-ii). The copolymer (A) used in the polymer composition (X) may be one type or two or more types. When two or more types of copolymers (A) are used, each of the copolymers should satisfy the following requirements (Ai) and (A-ii).

[0028] [Requirements (Ai)] Requirement (Ai): The content of structural units (i) derived from 4-methyl-1-pentene is 97.5 mol% or more and less than 100 mol%, and the content of structural units (ii) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 0 mol% and 2.5 mol% or less, provided that the total content of the structural units (i) and (ii) is 100 mol%. The content of the structural unit (i) is preferably from 97.5 to 99.5 mol %, more preferably from 97.5 to 99.2 mol %, and even more preferably from 97.7 to 99.0 mol %. The content of the structural unit (ii) is preferably from 0.5 to 2.5 mol %, more preferably from 0.8 to 2.5 mol %, and even more preferably from 1.0 to 2.3 mol %. When the content of the structural unit (i) and the structural unit (ii) is within the above range, a polymer composition having excellent heat resistance and moldability can be easily obtained. For example, if the same amount of 4-methyl-1-pentene homopolymer is used instead of the copolymer (A), the moldability of the obtained composition tends to be poor. This is presumably because the crystallization speed of the 4-methyl-1-pentene homopolymer is fast, and the resin tends to be poorly elongated during molding.

[0029] As the ethylene and α-olefins having 3 to 20 carbon atoms, linear α-olefins are preferred, and examples thereof include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. Among ethylene and α-olefins having 3 to 20 carbon atoms, from the viewpoint of moldability, linear α-olefins having 6 to 20 carbon atoms are preferred, and linear α-olefins having 10 to 18 carbon atoms are more preferred. Specifically, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and the like are preferred, and 1-decene, 1-hexadecene, and 1-octadecene are more preferred. The structural unit (ii) contained in the copolymer (A) may be of one type or of two or more types.

[0030] The copolymer (A) may further contain structural units derived from other polymerizable compounds other than 4-methyl-1-pentene, ethylene and the α-olefins having 3 to 20 carbon atoms, provided that the object of the present invention is not impaired. When the copolymer (A) has a constituent unit derived from the other polymerizable compound, the constituent unit may be of one type or of two or more types. Examples of the other polymerizable compounds include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentene, vinylcyclohexane, and vinylnorbornane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene. Examples of non-conjugated polyenes include dicyclopentadiene, cyclohexadiene, dicyclooctadiene, methylenenorbornene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene.

[0031] In the copolymer (A), the content of the structural units derived from the other polymerizable compounds is usually 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less, based on 100 mol % of all structural units constituting the copolymer (A).

[0032] [Requirements (A-ii)] Requirement (A-ii): Intrinsic viscosity [η] measured in decalin at 135°C A is 1.0 to 5.0 dl / g. Intrinsic viscosity [η] A is preferably 1.0 to 4.0 dl / g, more preferably 1.0 to 3.0 dl / g. Intrinsic viscosity [η] A When the viscosity is within the above range, the polymer composition exhibits good fluidity during preparation and molding. In addition, when mixed with the 4-methyl-1-pentene copolymer (B) and the 4-methyl-1-pentene copolymer (C), the copolymer is easily melt-kneaded uniformly, which is believed to contribute to improving transparency and blow moldability. Intrinsic viscosity [η] Acan be adjusted, for example, by the amount of hydrogen added in the polymerization step for producing the copolymer (A).

[0033] <4-methyl-1-pentene copolymer (B)> The 4-methyl-1-pentene copolymer (B) (hereinafter also referred to as "copolymer (B)") satisfies the following requirements (Bi) to (B-iii). The copolymer (B) used in the polymer composition (X) may be one type or two or more types. When two or more types of copolymers (B) are used, each copolymer only needs to satisfy the following requirements (Bi) to (B-iii).

[0034] [Requirements (Bi)] Requirement (Bi): The content of structural units (iii) derived from 4-methyl-1-pentene is 91.0 mol% or more and less than 97.5 mol%, and the content of structural units (iv) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 2.5 mol% and not more than 9.0 mol%, provided that the total content of the structural units (iii) and (iv) is 100 mol%. The content of the structural unit (iii) is preferably from 91.0 to 96.0 mol %, and more preferably from 91.5 to 95.0 mol %. The content of the structural unit (iv) is preferably 4.0 to 9.0 mol %, and more preferably 5.0 to 8.5 mol %. When the content of the structural unit (iii) and the structural unit (iv) is within the above range, a polymer composition having excellent moldability can be easily obtained. For example, if the same amount of 4-methyl-1-pentene homopolymer is used instead of the copolymer (B), the moldability of the obtained composition tends to be poor. This is presumably because the crystallization speed of the 4-methyl-1-pentene homopolymer is fast, and the resin tends to be poorly elongated during molding.

[0035] Examples of the ethylene and α-olefins having 3 to 20 carbon atoms that are the raw materials for the structural unit (iv) include the same compounds as the ethylene and α-olefins having 3 to 20 carbon atoms described in the column for the structural unit (ii), and the preferred compounds are also the same. The structural unit (iv) contained in the copolymer (B) may be of one type or of two or more types.

[0036] The copolymer (B) may further contain structural units derived from other polymerizable compounds other than 4-methyl-1-pentene, ethylene and the α-olefins having 3 to 20 carbon atoms, provided that the object of the present invention is not impaired. When the copolymer (B) has a constituent unit derived from the other polymerizable compound, the constituent unit may be of one type or of two or more types. Examples of the other polymerizable compounds include the same compounds as those described in the section on copolymer (A).

[0037] In copolymer (B), the content of structural units derived from other polymerizable compounds is usually 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less, based on 100 mol % of all structural units constituting copolymer (B).

[0038] [Requirement (B-ii)] Requirement (B-ii): Intrinsic viscosity [η] measured in decalin at 135°C B is 2.0~5.0dl / g. Intrinsic viscosity [η] B is preferably 2.2 to 4.8 dl / g, more preferably 2.5 to 4.5 dl / g. Intrinsic viscosity [η] B When the intrinsic viscosity [η] is within the above range, the polymer composition shows good fluidity during preparation and molding. When the polymer is further mixed with the 4-methyl-1-pentene copolymer (A) and the 4-methyl-1-pentene copolymer (C), the intrinsic viscosity [η] contributes to improving the stretchability, and is easily melt-kneaded uniformly, which is believed to contribute to improving the transparency and blow moldability. In particular, the intrinsic viscosity [η] BWhen is equal to or more than the above lower limit, the polymer composition (X) has excellent stretchability when molded. Intrinsic viscosity [η] B can be adjusted, for example, by the amount of hydrogen added in the polymerization step for producing the copolymer (B).

[0039] [Requirements (B-iii)] Requirement (B-iii): Melting point (Tm B ) is 180°C or higher and less than 210°C. Melting point (Tm B ) is preferably 180 to 200°C, more preferably 180 to 195°C. Melting point (Tm B ) is within the above range, the polymer composition (X) containing the copolymer (B) and the molded article obtained from the polymer composition (X) have excellent blow moldability. Melting point (Tm B ) is specifically measured by the method described in the Examples below. Melting point (Tm B ) tends to depend on the stereoregularity of copolymer (B) and the content of structural unit (iv) in copolymer (B). For this reason, by using an olefin polymerization catalyst described later and further controlling the content of structural unit (iv), the melting point (Tm B ) can be adjusted.

[0040] <4-methyl-1-pentene copolymer (C)> The 4-methyl-1-pentene copolymer (C) (hereinafter also referred to as "copolymer (C)") satisfies the following requirements (Ci) to (C-iii). The copolymer (C) used in the polymer composition (X) may be one type or two or more types. When two or more types of copolymers (C) are used, each copolymer should satisfy the following requirements (Ci) to (C-iii).

[0041] Requirements Requirement (Ci): The content of structural units (v) derived from 4-methyl-1-pentene is 75.0 mol% or more and less than 91.0 mol%, and the content of structural units (vi) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 9.0 mol% and not more than 25.0 mol%, provided that the total content of the structural units (v) and the structural units (vi) is 100 mol%. The content of the structural unit (v) is preferably at least 77.0 mol % and less than 91.0 mol %, and more preferably from 80.0 to 90.0 mol %. The content of the structural unit (vi) is preferably more than 9.0 mol % and not more than 23.0 mol %, and more preferably 10.0 to 20.0 mol %. When the content of the structural unit (v) and the structural unit (vi) is within the above range, a polymer composition having excellent moldability can be easily obtained while maintaining the properties (e.g., transparency, releasability) of the homopolymer of 4-methyl-1-pentene. For example, when the same amount of the homopolymer of 4-methyl-1-pentene is used instead of the copolymer (C), the moldability of the obtained composition tends to be worse than when the copolymer (C) is used. This is presumably because the homopolymer of 4-methyl-1-pentene has a fast crystallization rate, which tends to make the resin less stretchable during molding.

[0042] Examples of the ethylene and α-olefins having 3 to 20 carbon atoms that are the raw materials for the structural unit (vi) include the same compounds as the ethylene and α-olefins having 3 to 20 carbon atoms described in the column for the structural unit (ii), and the preferred compounds are also the same. Among ethylene and the α-olefins having 3 to 20 carbon atoms, 1-decene is particularly preferred because it allows for the easy production of a polymer composition (X) having excellent stretchability and a molded article. The structural unit (vi) contained in the copolymer (C) may be of one type or of two or more types.

[0043] The copolymer (C) may further contain structural units derived from other polymerizable compounds other than 4-methyl-1-pentene, ethylene and the α-olefins having 3 to 20 carbon atoms, provided that the object of the present invention is not impaired. When the copolymer (C) has a constituent unit derived from the other polymerizable compound, the constituent unit may be of one type or of two or more types. Examples of the other polymerizable compounds include the same compounds as those described in the section on copolymer (A).

[0044] In the copolymer (C), the content of structural units derived from other polymerizable compounds is usually 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less, based on 100 mol % of all structural units constituting the copolymer (C).

[0045] [Requirement (C-ii)] Requirement (C-ii): Intrinsic viscosity [η] measured in decalin at 135°C C is 0.1 dl / g or more and less than 2.0 dl / g. Intrinsic viscosity [η] C is preferably 0.5 to 1.9 dl / g, and more preferably 1.0 to 1.8 dl / g or less. Intrinsic viscosity [η] C When the copolymer (C) having a molecular weight of 1,000 to 1,000 mol / L is used together with the copolymer (A) and the copolymer (B), a polymer composition having excellent moldability (particularly injection moldability) can be easily obtained, and a molded article having low heat shrinkage while having a well-balanced excellent mechanical properties (particularly tensile properties and bending properties), impact resistance, transparency and heat resistance can be easily formed. Intrinsic viscosity [η] C can be adjusted, for example, by the amount of hydrogen added in the polymerization step for producing the copolymer (C).

[0046] [Requirement (C-iii)] Requirement (C-iii): Melting point (Tm C ) is not observed. Melting point (Tm C) is not observed, the polymer composition (X) containing the copolymer (C) is easily stretched, and the thickness distribution of the molded article formed from the polymer composition (X) tends to be narrow. Melting point (Tm C ) is specifically measured by the method described in the Examples below. Melting point (Tm C ) tends to depend on the stereoregularity of the copolymer (C) and the content of the structural unit (vi) in the copolymer (C). For this reason, by using an olefin polymerization catalyst described later and further controlling the content of the structural unit (vi), the melting point (Tm C ) can be adjusted.

[0047] <Methods for Producing Copolymer (A), Copolymer (B) and Copolymer (C)> Copolymer (A), copolymer (B) and copolymer (C) can each be obtained by polymerizing 4-methyl-1-pentene, ethylene other than 4-methyl-1-pentene, an α-olefin having 3 to 20 carbon atoms, and, if necessary, the other polymerizable compound, in the presence of an olefin polymerization catalyst, by a known method.

[0048] Examples of olefin polymerization catalysts that can be used in the production of copolymer (A), copolymer (B) and copolymer (C) include metallocene catalysts.Preferred metallocene catalysts include, for example, the metallocene catalysts described in International Publication No. 2001 / 053369, International Publication No. 2001 / 027124, JP-A-3-193796, JP-A-2-41303, International Publication No. 2006 / 025540, International Publication No. 2014 / 050817, International Publication No. 2014 / 123212, and International Publication No. 2017 / 150265.

[0049] Incidentally, any of the copolymers (A), (B) and (C) may be polymerized in the presence of other polymers by multi-stage polymerization. For example, in the first polymerization stage, the copolymer (A) may be polymerized, the copolymer (B) may be polymerized in the presence of the copolymer (A), and the copolymer (C) may be polymerized in the presence of the copolymer (A) and the copolymer (B). Similarly, the copolymer (A) may be polymerized in the presence of one or more of the copolymers (B) and (C), and the copolymer (B) may be polymerized in the presence of one or more of the copolymers (A) and (C).

[0050] Copolymer (A), copolymer (B) and copolymer (C) may be a commercially available 4-methyl-1-pentene copolymer (eg, TPX manufactured by Mitsui Chemicals, Inc.). The copolymer (A) may be a copolymer (A) prepared by heat-treating a 4-methyl-1-pentene copolymer once produced with the catalyst, etc., using an extruder, a mixer, etc. Alternatively, the copolymer (A) may be prepared by heat-treating a commercially available 4-methyl-1-pentene copolymer (e.g., TPX manufactured by Mitsui Chemicals, Inc.) using an extruder, a mixer, etc.

[0051] <Amounts of Various Components Blended in Polymer Composition (X)> The content of the copolymer (A) in the polymer composition (X) is from 15 to 45% by mass, preferably from 20 to 40% by mass, and more preferably from 24 to 40% by mass. The content of the copolymer (B) in the polymer composition (X) is from 35 to 80% by mass, preferably from 40 to 70% by mass, and more preferably from 44 to 65% by mass. The content of the copolymer (C) in the polymer composition (X) is from 5 to 30% by mass, preferably from 7 to 25% by mass, and more preferably from 9 to 25% by mass. However, the content of each of the copolymers is the content when the total content of copolymer (A), copolymer (B) and copolymer (C) is taken as 100 mass %. When the contents of copolymer (A), copolymer (B) and copolymer (C) are within the above ranges, a molded product having excellent heat resistance and mechanical properties in a well-balanced manner can be easily formed.

[0052] The total content of the copolymer (A), the copolymer (B) and the copolymer (C) in the polymer composition (X) is usually 90.1 mass% or more, preferably 97.0 mass% or more, more preferably 98.0 mass% or more, and even more preferably 99.0 mass% or more, based on 100 mass% of the polymer composition (X). The upper limit of the total content of copolymer (A), copolymer (B) and copolymer (C) in polymer composition (X) may be 100% by mass. When polymer composition (X) contains the following additives, the upper limit varies depending on the content of the following additives.

[0053] <Additives> The polymer composition (X) may contain conventionally known additives. Examples of the additives include other polymer components than the copolymer (A), the copolymer (B) and the copolymer (C), secondary antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, fillers and hydrochloric acid absorbents. The content of the additives is not particularly limited, but is usually 0 to 10 parts by mass, preferably 0 to 3.1 parts by mass, for each of 100 parts by mass of the total of copolymer (A), copolymer (B) and copolymer (C). The additives may each be used alone or in combination of two or more kinds.

[0054] [Other polymer components] The polymer composition (X) may further contain other polymer components in addition to the copolymer (A), the copolymer (B) and the copolymer (C). Examples of the other polymer components include 4-methyl-1-pentene copolymers other than the copolymers (A), (B) and (C). When the polymer composition (X) contains the other polymer components, the content of the polymer components is usually 3.0 parts by mass or less, preferably 2.0 parts by mass or less, and more preferably 1.0 part by mass or less, per 100 parts by mass of the total content of the copolymers (A), (B) and (C).

[0055] <Method for producing polymer composition (X)> The polymer composition (X) can be produced, for example, by mixing the copolymer (A), the copolymer (B) and the copolymer (C) with the additives as necessary. A mixture of two or more of the copolymers (A), (B) and (C) can also be obtained by the multi-stage polymerization method.

[0056] The method for mixing the components includes various known methods, such as a method for mixing the components using an apparatus such as a plastomill, a Henschel mixer, a V-blender, a ribbon blender, a tumbler, a blender, a kneader-ruder, etc. After the mixing, the resulting mixture may be further melt-kneaded using an apparatus such as a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc., and the resulting melt-kneaded product may be granulated or pulverized.

[0057] <Molded body> The molded article according to the present invention (hereinafter also referred to as the "present molded article") contains the polymer composition (X). The present molded article can be obtained using the polymer composition (X) by known thermoforming methods such as extrusion molding, injection molding, inflation molding, blow molding, extrusion blow molding, injection blow molding, stretch blow molding, press molding, stamping molding, vacuum molding, calendar molding, filament molding, foam molding, and powder slush molding.

[0058] Since the polymer composition (X) has excellent moldability, the molded article can be suitably produced by the above-mentioned molding method, and in particular, the desired molded article can be easily formed by injection molding, injection blow molding, and stretch blow molding. For this reason, in order to better exert the effects of the present invention, it is preferable that the present molded product is a blow molded product obtained by blow molding, in particular an injection blow molded product or a stretch blow molded product obtained by injection blow molding or stretch blow molding.

[0059] <Blow molded product> A preferred embodiment of the present molded article is a blow molded article, and preferred examples of the blow molded article include an injection blow molded article and a stretch blow molded article. A specific example of the blow molded article is a hollow molded article.

[0060] <Method of manufacturing blow molded article> The blow molded article can be produced by any commonly known blow molding method except for using the polymer composition (X). A specific example of blow molding is a method in which a preform (e.g., a parison) is molded from the polymer composition (X), the preform is sandwiched between metal dies, pressurized gas is fed into the heated preform, the polymer composition (X) is brought into close contact with the metal die, and then the preform is cooled to form a hollow molded article. Methods for molding a preform include injection molding, extrusion molding, and the like, and corresponding blow molding methods include injection blow molding, extrusion blow molding, and the like. Also included is stretch blow molding in which a stretching step is performed when pressurized gas is fed into the heated preform. In this stretch blow molding, for example, when performing biaxial stretch blow molding, a stretch rod is inserted deep inside the preform to perform vertical stretching, and pressurized gas is simultaneously blown in the horizontal direction to expand the preform so as to stretch it horizontally as well, thereby obtaining a biaxially stretched hollow molded body.

[0061] In addition, blow molding has traditionally been broadly divided into two methods: blow molding (two-stage method), in which a preform is first molded and then cooled to obtain a preform (cold parison), which is then heated again in a mold before pressurized gas is pumped in; and direct blow molding (one-stage method), in which a parison is molded from molten resin and then pressurized gas is immediately pumped into the heated preform (hot parison). The two-stage method is a method with good production efficiency because the parison manufacturing process and the pressurized gas blowing process can be separated, but the cold parison needs to be reheated, and there is room for improvement in terms of production costs (energy loss). On the other hand, the one-stage method is an excellent method in that there is no energy loss, but there is room for improvement in that the resins that can be used are limited and the shapes that can be stretch-blown are limited. For this reason, in order to achieve both production efficiency and versatility, the so-called 1.5-stage method is also used, in which after a preform is manufactured once, it is transferred to a device for a process other than the device for the preform manufacturing process, and the pressurized gas blowing process is performed on the preform in a state that is not completely cooled (semi-heated state).

[0062] The blow molding may be any of a one-stage method, a 1.5-stage method, and a two-stage method. Also suitable for the blow molding are injection blow molding, which is a method of forming a preform by injection molding and then performing a pressurized gas blowing (blowing) step, and stretch blow molding, which is a method of accompanying a stretching step when performing the pressurized gas blowing (blowing) step.

[0063] A suitable example of the method for producing the present molded article (particularly the injection blow molded article) includes a method comprising a step (1) of forming a preform by injection molding the polymer composition (X) and a step (2) of forming a blow molded article by blow molding the obtained preform.

[0064] [Process (1)] The step (1) is preferably a step of melting the polymer composition (X) and injection-molding the polymer composition (X) into a mold to form a preform. The temperature at which the polymer composition (X) is melted and injected is usually 260 to 320° C. The mold temperature may be set to, for example, (20 to 80° C.). The molded preform is removed from the mold, and the draft angle of the preform in the mold is preferably 2.0 to 5.0°. By making the draft angle relatively large, it becomes possible to remove the preform at a high temperature, and furthermore, scratches during removal can be reduced. Furthermore, by making the draft angle relatively large, the preform can be easily removed from the mold, and therefore, when using the 1.5 stage method, it becomes easier to ensure the heat retained in the preform required for the blowing process.

[0065] [Process (2)] In step (2), it is desirable to first include a surface temperature adjustment step of adjusting the surface temperature of the preform formed in step (1) to preferably 130 to 220°C, more preferably 135 to 215°C, and more preferably 140 to 210°C. By adjusting the surface temperature of the preform to the above range, the preform can be softened and easily blow molded. If the surface temperature of the preform is lower than the above range, it is preferable to reheat the preform using an infrared heater or the like as appropriate until the surface temperature reaches the above range. The surface temperature of the preform can be measured, for example, by imaging the preform from a distance of 1 m from the surface of the preform using an infrared camera FLIR C5 manufactured by FLIR Systems Japan Co., Ltd.

[0066] In the step (2), it is preferable to carry out blow molding after carrying out the surface temperature adjustment step. The temperature during the blow molding (blow temperature) is usually 130 to 220° C., preferably 135 to 215° C., and more preferably 140 to 210° C. When the blow temperature is within the above range, surface roughness during blow molding caused by insufficient heat can be suppressed, and further, poor appearance caused by uneven thickness or deformation due to thermal deformation of the preform can be suppressed.

[0067] Blow molding is usually carried out by blowing air into the mold. The blowing may be performed in one stage or in two or more stages. When performing in two or more stages, the blowing pressure in each stage may be the same or different. The blowing pressure may be appropriately set according to the shape of the desired molded body, etc.

[0068] Step (2) may be stretch blow molding in which a stretching step is carried out during the pressurized gas blowing step. A specific example of stretch blow molding is a method in which a preform is first placed in a blow molding die, a stretch rod is inserted through the opening of the preform, stretched in the axial direction of the stretch rod (the longitudinal direction of the preform), and then, after or in parallel with the longitudinal stretching, gas is injected into the blow molding die to stretch the preform in the lateral direction (the radial direction of the preform) while molding the preform into a desired shape. This method allows biaxial stretching, which improves the strength of the resulting molded product.

[0069] In the stretch blow molding, in order to achieve uniform stretching, it is desirable to carry out the stretching treatment so that the stretch ratio in the longitudinal direction is preferably 1.1 to 2.0 times, more preferably 1.1 to 1.9 times, and further preferably 1.1 to 1.8 times. The stretch ratio in the longitudinal direction is calculated as follows. Stretch ratio in the longitudinal direction = (height of molded body (bottle)) / (height of preform)

[0070] In the stretch blow molding, in order to achieve uniform stretching, it is desirable to carry out the stretching treatment so that the stretch ratio in the transverse direction is preferably 1.1 to 3.5 times, more preferably 1.2 to 3.0 times, and further preferably 1.3 to 2.8 times. When the molded article is a bottle, the stretch ratio in the transverse direction is calculated as follows. Transverse stretch ratio = (bottle circumference) / (preform circumference)

[0071] The product of the stretch ratio in the longitudinal direction and the stretch ratio in the transverse direction in the stretch blow molding (total stretch ratio) is preferably 1.2 to 6.0 times, more preferably 1.5 to 5.5 times, and further preferably 1.8 to 5.0 times. When the total stretch ratio is within the above range, a molded article having excellent dimensional accuracy with reduced thickness unevenness can be easily formed.

[0072] The present molded article may be an injection blow molded article having at least one layer of the polymer composition (X), which is obtained by, for example, co-injecting two or more resin compositions containing the polymer composition (X) to form a multi-layer preform, followed by blow molding.

[0073] <Applications of molded products> The molded article, like the molded article obtained from the conventional composition containing a 4-methyl-1-pentene polymer, is excellent in heat resistance, chemical resistance, gas permeability, food hygiene, etc., and further has excellent mechanical strength (particularly tensile properties and bending properties), impact resistance, and transparency, and is particularly resistant to thermal shrinkage. Therefore, the molded article can be suitably used in applications requiring one or more of these properties, and specifically, can be suitably used in applications such as physicochemical containers (laboratory equipment), cell culture containers, beverage containers for infants and young children such as baby bottles and mugs, food refill containers, containers for aromatics, cosmetic containers, and gas-permeable containers for ornamental plants. EXAMPLES

[0074] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0075] [Manufacturing Examples 1 to 5] In accordance with the polymerization method described in Comparative Example 1 (

[0158] ) of WO 2017 / 150265, copolymers (A-1), (B-1), (B-2), (C-1) and (C-2) were synthesized by changing the proportions of 4-methyl-1-pentene, 1-decene and hydrogen used so that the physical properties of the resulting 4-methyl-1-pentene copolymers would be the values ​​listed in Table 1.

[0076] <Method of measuring physical properties of polymer> The physical properties of the polymers used in the following Examples and Comparative Examples were measured as follows. The various physical properties are shown in Table 1.

[0077] <Composition> For each of the polymers used in the examples and comparative examples, the content of structural units derived from 4-methyl-1-pentene (hereinafter also referred to as "4-methyl-1-pentene amount") and the content of structural units derived from ethylene and α-olefins having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene; hereinafter also referred to as "comonomer species") (hereinafter also referred to as "comonomer amount") were measured using the following apparatus and conditions: 13 The C-NMR spectrum was measured. 13 The amount of 4-methyl-1-pentene and the amount of comonomer were determined by C-NMR spectrum.

[0078] Equipment: JEOL Ltd. ECP500 nuclear magnetic resonance spectrometer Solvent: o-dichlorobenzene / heavy benzene (80% by volume / 20% by volume) mixed solvent Sample concentration: 55mg / 0.6mL Measurement temperature: 120℃ Observation kernel: 13 C(125MHz) Sequence: Single pulse proton decoupling Pulse width: 4.7μsec (45° pulse) Repeat time: 5.5 seconds Number of times: 10,000 or more Chemical shift reference value: 27.50 ppm

[0079] <Intrinsic viscosity [η]> The intrinsic viscosity [η] was measured at 135° C. using decalin as a solvent. Specifically, about 20 mg of each of the polymers used in the examples and comparative examples was weighed out, dissolved in 15 mL of decalin, and heated to a specific viscosity of η SP The decalin solution was diluted with 5 mL of decalin solvent, and the specific viscosity η was measured in the same manner. SP This dilution procedure was repeated two more times, and the η SP The value of / C was calculated as the intrinsic viscosity (see the formula below). [η]=lim(η SP / C) (C→0)

[0080] <Melting point (Tm)> For each of the polymers used in the examples and comparative examples, the exothermic and endothermic curves were obtained using a DSC measuring device (DSC220C) manufactured by Seiko Instruments Inc., and the temperature at the maximum melting peak position during heating was taken as the melting point (Tm). The measurement was carried out as follows. About 5 mg of the polymer was placed in an aluminum pan for measurement, and the temperature was increased from 20° C. to 280° C. at a heating rate of 10° C. / min, and after being held at 280° C. for 5 minutes, the temperature was decreased to 20° C. at a cooling rate of 10° C. / min. Next, after being held at 20° C. for 5 minutes, the temperature was increased again from 20° C. to 280° C. at a heating rate of 10° C. / min, and the temperature was decreased to 50° C. at a cooling rate of 50° C. / min. The temperature at the apex of the melting peak that appeared during the second heating was taken as the melting point (Tm). When multiple melting peaks were detected, the temperature with the maximum peak temperature was taken as the melting point (Tm).

[0081] [Table 1]

[0082] [Example 1] A twin-screw extruder (PCM43, manufactured by Ikegai Corporation, screw diameter: 43 mm) was charged with 40% by mass of copolymer (A-1), 38% by mass of copolymer (B-1), and 22% by mass of copolymer (C-1). Then, the polymer composition was obtained by melt-kneading at 280 °C and a rotational speed of 200 rpm using the twin-screw extruder. In addition, in Table 2, the "total amount of comonomer in the composition" is the sum of the product of the comonomer amount (content of structural units derived from ethylene and α-olefins having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene)) [mol%] in each copolymer constituting the polymer composition and the content [mass%] / 100 of each copolymer constituting the polymer composition.

[0083] [Examples 2 to 4 and Comparative Examples 1 to 5] A polymer composition was obtained in the same manner as in Example 1, except that the types and amounts of the copolymers used were changed as described in Table 2.

[0084] [Preparation of Injection Test Specimens] Using a 70-ton injection molding machine (M70B) manufactured by Meiki Co., Ltd., each of the obtained polymer compositions was injected under the conditions of a cylinder temperature of 280 °C and a mold temperature of 60 °C to form square plates with thicknesses of 2 mm, 3 mm, 3.2 mm, or 1 / 4 inch, thereby preparing injection test specimens.

[0085] [Tensile Test] Using injection test specimens with a thickness of 2 mm, ASTM D638-compliant ASTM-4 dumbbell-shaped test specimens were prepared. A universal tensile testing machine 3380 manufactured by Instron Corporation was used to conduct a tensile test under the conditions of a tensile speed of 50 mm / min and a measurement temperature of 23 °C, and the tensile modulus, tensile breaking stress, and tensile elongation at break were measured. The results are shown in Table 2.

[0086] [Izod Impact Test (Without Notch)] Using a 3 mm thick injection test piece, an Izod impact test was performed in accordance with ASTM D 4812 using a digital impact tester DG-IB model manufactured by Toyo Seiki Seisakusho Co., Ltd., under the conditions of hammer capacity: 3.92 J, idling angle: 148.9°, and test temperature: 23°C, to measure the unnotched Izod impact strength. The results are shown in Table 2.

[0087] <Bending elasticity test> A bending test was performed using an injection test piece having a thickness of 3.2 mm in accordance with ASTM D 790 using an AG-X plus model manufactured by Shimadzu Corporation at a test speed of 1.3 mm / min and a measurement temperature of 23°C to measure the bending modulus. The results are shown in Table 2.

[0088] <Heat distortion temperature test> Using a 1 / 4 inch thick injection test piece, a heat distortion temperature test was carried out in accordance with ASTM D648 using an HDT measuring device manufactured by Yasuda Seiki Seisakusho Co., Ltd., under the conditions of a heating rate of 50°C / hour and a test load of 0.45 MPa, to measure the heat distortion temperature (HDT). The results are shown in Table 2.

[0089] <Total haze, internal haze, total light transmittance test> Using an injection test piece with a thickness of 2 mm, the total amount of transmitted light passing through the test piece was measured in accordance with JIS K 7136:2000 using a haze / transmittance meter HM-150 (D65 light source) manufactured by Murakami Color Research Laboratory Co., Ltd. The total light transmittance was calculated using the following formula. In addition, the proportion of transmitted light that deviated from the incident light by 2.5° or more due to forward scattering among the transmitted light that passed through the test piece was measured to determine the total haze. The internal haze was measured in the same manner as the total haze, except that it was measured in benzyl alcohol. The results are shown in Table 2. Total light transmittance (%) = (total transmitted light amount) / (incident light amount) × 100

[0090] <Blow moldability test> Each of the obtained polymer compositions was molded using a one-step injection blow molding machine manufactured by Nissei ASB Machinery Co., Ltd. under conditions of cylinder temperature: 280°C and mold temperature: 40°C to produce a preform having an outer diameter of 24 mm, a height of 107 mm, and a mass of 18 g.

[0091] The surface temperature of the prepared preform was adjusted to 140°C, and the preform was blow molded using a mold capable of forming a 330cc container (longitudinal stretch ratio: 1.7 times, transverse stretch ratio: 2.4 times, total stretch ratio: 4.1 times). The blow moldability was evaluated according to the following criteria. The results are shown in Table 2. The air blowing was performed in two stages, with a primary pressure of 0.4 MPa and a secondary pressure of 3.0 MPa. The surface temperature of the preform during blow molding was measured by capturing an image of the preform from a distance of 1 m using an infrared camera FLIR C5 manufactured by FLIR Systems Japan Inc. [Evaluation Criteria] ○: Stretch blow molding was possible ×: Stretch blow molding was not possible

[0092] <Heat shrinkage test> The containers (bottles) obtained by the blow molding were autoclaved at 121°C for 20 minutes using an autoclave machine LSX-300 manufactured by Tomy Kogyo Co., Ltd. Before autoclaving, a mark was made on the bottle at the position where the content volume was 200 mL, and after autoclaving, water was poured up to the mark, and the change in mass was regarded as the volume change, and the volume change rate before and after autoclaving was calculated. The calculated volume change rate was evaluated according to the following criteria. The results are shown in Table 2. ○: Volume change rate is less than 5% ×: Volume change rate is 5% or more

[0093] [Table 2]

Claims

1. 15 to 45% by mass of a 4-methyl-1-pentene copolymer (A) satisfying the following requirements (A-i) and (A-ii); 35 to 80% by mass of a 4-methyl-1-pentene copolymer (B) satisfying the following requirements (Bi) to (B-iii); 5 to 30% by mass of a 4-methyl-1-pentene copolymer (C) satisfying the following requirements (C-i) to (C-iii) (where the total of the copolymers (A) to (C) is 100% by mass): The polymer composition (X). Requirement (A-i): The content of structural units (i) derived from 4-methyl-1-pentene is 97.5 mol% or more and less than 100 mol%, and the content of structural units (ii) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 0 mol% and 2.5 mol% or less (the total content of the structural units (i) and (ii) is 100 mol%). Requirement (A-ii): Intrinsic viscosity [η] measured in decalin at 135 ° C. A is 1.0 to 5.0 dl / g Requirement (B-i): The content of structural units (iii) derived from 4-methyl-1-pentene is 91.0 mol% or more and less than 97.5 mol%, and the content of structural units (iv) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 2.5 mol% and 9.0 mol% or less (the total content of the structural units (iii) and (iv) is 100 mol%). Requirement (B-ii): Intrinsic viscosity [η] measured in decalin at 135 ° C. B is 2.0 to 5.0 dl / g Requirement (B-iii): Melting point (Tm B ) is 180°C or more and less than 210°C Requirement (C-i): The content of the structural unit (v) derived from 4-methyl-1-pentene is 75.0 mol% or more and less than 91.0 mol%, and the content of the structural unit (vi) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) is more than 9.0 mol% and not more than 25.0 mol% (the total content of the structural unit (v) and the structural unit (vi) is 100 mol%). Requirement (C-ii): Intrinsic viscosity [η] measured in decalin at 135 ° C. C is 0.1 dl / g or more and less than 2.0 dl / g Requirement (C-iii): Melting point (Tm C ) is not observed

2. the total content of all structural units (I) derived from 4-methyl-1-pentene contained in the polymer composition (X) is 90.0 to 96.0 mol %, the total content of all structural units (II) derived from ethylene and an α-olefin having 3 to 20 carbon atoms (excluding 4-methyl-1-pentene) contained in the polymer composition (X) is 4.0 to 10.0 mol % (the total content of the structural units (I) and (II) is taken as 100 mol %); The polymer composition (X) according to claim 1.

3. A molded article comprising the polymer composition (X) according to claim 1 or 2.

4. The molded article according to claim 3, which is a blow molded article.

5. It is a stretch blow molded article, The product of the stretch ratio in the longitudinal direction and the stretch ratio in the transverse direction of the stretch blow molded body is 1.2 to 6.0 times. The molded article according to claim 3.

6. forming a preform by injection molding the polymer composition (X) according to claim 1 or 2; A step of forming a blow molded article by blow molding the obtained preform. A method for producing a molded body, comprising the steps of:

Citation Information

Patent Citations

  • 4-methyl-1-pentene copolymer composition

    JP2018162408A

  • 4-methyl-1-pentene (CO)polymer composition, and film and hollow molded body, each of which is formed from 4-methyl-1-pentene (CO)polymer composition

    WO2013099876A1

  • 4-methyl-1-pentene polymer particles and method of producing 4-methyl-1-pentene resin

    WO2019198694A1

Cited By

  • Semiconductor device

    CN122784156A